Hazardous gas detection using gas sensors arrays and fuzzy-based classification - Mohamed R.R.; Mohamed M.A.; Hashim W.; Rahim A.; Fuad M.S. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
This paper presents hazardous gas detection using gas sensors arrays and fuzzy-based classification. This research is an automation of hazardous gas detection using electronic nose. Gases surround us could either hazard or benefit our health. Gas detection is an important issue, as humans should not breathe in hazardous gases in order to maintain their health. Hence, there must be an indicator to show the hazardous level of certain gases so that people can avoid and minimize the impact on their health. In this paper, hazardous gas detection is implemented by using gas sensor arrays and fuzzy-based classification. A classification for the electronic nose (e-nose) is developed in order to classify gases and determine the level of hazard of gases. The results found that e-nose system is able to differentiate hazardous level of chosen gases which are LP gas and CO gas. BEIESP.